Untargeted metabolomics reveal the therapeutic effects of Ermiao wan categorized formulas on rats with hyperuricemia. (5th December 2021) - Shan, Baixi; Chen, Ting; Huang, Bixia; Liu, Yang; Chen, Jun
Abstract: Ethnopharmacological relevance: Ermiao wan (2 MW) is one of the most frequently prescription in traditional Chinese medicine (TCM) to treat hyperuricemia. Sanmiao wan (3 MW) and Simiao wan (4 MW), two modified Ermiao wan, also show good clinical effects in the treatment of gout and hyperuricemia. However, their uric acid lowering effects and potential action mechanism still need to be systematically investigated. Aim of the study: The aim of present study was to analyze and compare the uric acid-lowering effects of 2 MW, 3 MW and 4 MW in rat with high fructose combined with potassium oxonate (HFCPO)-induced hyperuricemia and their possible mechanisms through plasma metabolomics methods. Materials and methods: HFCPO-induced hyperuricemia rat model was established to evaluate the therapeutic effects of Ermiao wan categorized formulas (ECFs, including 2 MW, 3 MW and 4 MW). Body weight, blood uric acid, creatinine, urine uric acid and urine creatinine levels and histopathological parameters of rats were assessed. Plasma untargeted metabolomics based on ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-QTOF/MS) was established to collect the metabolic profiles of rats and explore the metabolic changes that occurred after each ECFs treatment. Results: Oral administration of ECFs could decrease the level of blood uric acid, creatinine and increase the level of urine uric acid and urine creatinine in varying degrees, and alleviated hepatocyte steatosis and atrophy and degeneration of glomerulus, vacuolar degeneration of renal tubular epithelial cells in HFCPO-induced hyperuricemia rats. Plasma untargeted metabolomics analysis showed that significant alterations were observed in metabolic signatures between the HFCPO-induced hyperuricemia group and control group. Thirty five potential biomarkers in rat plasma were identified in the screening by principal component analysis (PCA), partial least squares discrimination analysis (PLS-DA) and orthogonal partial least squares discrimination analysis (OPLS-DA). Differential metabolites related to hyperuricemia, including acylcarnitines and amino acid related metabolites, were further used to indicate relevant pathways in hyperuricemia rats, including tryptophan metabolism, arginine biosynthesis, purine metabolism, arginine and proline metabolism, beta-alanine metabolism, citrate cycle (TCA cycle), glycerophospholipid metabolism and linoleic acid metabolism. 2 MW, 3 MW and 4 MW could invert the pathological process of hyperuricemia to varying degrees through in part regulating the perturbed lipid metabolic pathway. 4 MW were better than 2 MW and 3 MW in the intervention of the disordered tricarboxylic acid metabolism and purine metabolism caused by hyperuricemia. Conclusion: In summary, ECFs treatment could effectively alleviate symptoms of hyperuricemia and regulate metabolic disorders in HFCPO-induced hyperuricemia rats. Graphical abstract: Schematic illustration of the treatment of hyperuricemia with Ermiao wan categorized formulas. Image 1 Highlights: Application of metabonomics in plasma metabolism of hyperuricemic rats. Mechanism of ECFs in the treatment of hyperuricemia by regulating metabolic pathways. 35 metabolites were tentatively identified and regarded as potential biomarkers of hyperuricemia. purine metabolism and TCA cycle, etc. were modulated by ECFs treatment in hyperuricemia rats.